The 1st SAU Annual Conference on Urological Research: SAU 2023 Conference Report - Liu, Xiaoqi; Li, Benyi (Serican Journal of Medicine, 2024)
In the fall of 2022, Dr. Benyi Li from the University of Kansas registered the scientific society with the title of Serican Academy of Urology (SAU), an international non-profit organization. The SAU is dedicated to uniting clinicians and basic scientists to tackle diseases related to the genitourinary tract. Prostate cancer, particularly castration-resistant prostate cancer and neuroendocrine prostate cancer, remains a significant public health issue. The academy held its first annual conference on December 26-29, 2023, in Cancun, Mexico. The conference was chaired by Dr. Xiaoqi Liu from the University of Kentucky, with generous sponsorship from SinoBiological, MedChemExpress, and Admera Health. Aiming to address the most urgent issues related to prostate cancer, the conference focused on topics such as epigenetics, lineage plasticity, therapy resistance, novel target identification, immunotherapy, and emerging technologies in the field. In honor of the late Dr. Changdeng Hu from Purdue University, one of the SAU founder members, Dr. Jiaoti Huang from Duke University presented a keynote address on developing grant applications through collaboration with pathologists. The Career Development Forum provided a platform for discussing career navigation and leadership development for the next generation of prostate cancer researchers. The conference concluded with a banquet, including an awards ceremony and committee reports.